Imbas Konsistensi Hukuman Mati pada Hubungan Bilateral dalam Kasus Narkoba - Moh Rosyid (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
This article discusses about the debate over death penalty in the drug abuse cases. The Constitutional Court on October 30th, 2007 on the judicial review of Article 80 of the Law No 22/1997 on Drug declared that death penalty is not violating the Constitution which guarantees the right to life. Furthermore, Indonesia has ratified the International convention on narcotics and psychotropic. On the other hand, the opponent of death penalty argues that death penalty violates Article 28A of the Amendment of the Constitution that all people have the right to life. Secondly, death penalty is cruel and inhumane. Thirdly, there is possibility for false trial, and fourth, death penalty is not in-line with the reformation of penal law which imposes on restorative justice instead of retributive. Fifth, the effect is just a myth and sixth, the family becomes co-victim. Seventh, death penalty also threatened Indonesian living abroad and the last, death penalty cause the loss of Indonesia in International relations.